ajhissues 2018
DOI: 10.26875/ajhi112017vi
|View full text |Cite
|
Sign up to set email alerts
|

Demographic and clinical profile of craniofacial clefts at Comprehensive Rehabilitation Service in Uganda

Abstract: Background: The true incidence of Craniofacial cleft (CFC) is unknown because of their scarcity and because of the difficulty in recognizing sometimes subtle physical findings in mild malformations. Craniofacial anomalies in the African population are reported infrequently. Aim: To contribute to the general literature on rare CFC in Uganda and Africa. Methods: we conducted a retrospective search of patient data over the period 2005 to May 2017 in the unit of plastic surgery of CoRSU (Comprehensive Rehabilitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 6 publications
2
3
0
Order By: Relevance
“…The present study revealed no gender predilection in the occurrence of rare craniofacial cleft, which is consistent with previous studies [8,9,11]. However, some researchers reported a male predominance [10,12].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The present study revealed no gender predilection in the occurrence of rare craniofacial cleft, which is consistent with previous studies [8,9,11]. However, some researchers reported a male predominance [10,12].…”
Section: Discussionsupporting
confidence: 93%
“…The wide variation in age of the investigated patients was similar to findings from African studies [8,11], which was in contrast with other reports where most patients presented less than 2 years [10,12]. Delayed presentation in our environment remains a challenge to achieve optimal care, which is partly due to religious, socio-cultural, and economic factors.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations